Evaluation of service frost resistance of ceramic facing tiles - Mačiulaitis, Romualdas; Kičaite, Asta; Nagrockiene, Džigita; Kudabiene, Gema (Journal of Civil Engineering and Management, 2004)
The problem of frost resistance is relevant to facing materials, especially glazed ceramic tiles. Analysing the processes of ceramic tile destruction it is important to take into account the primary destruction symptoms. New estimation of service frost resistance of ceramie tile according to residual surface and residual mass of the tile after a certain number of simulated service cycles is presented in the paper. Applying the new estimation, the forecast of frost resistance under extremely unfavourable service conditions may be performed. As for other ceramie products regarding frost resistance, one of the most important parameters is the reserve of pore volume. For a rapid estimation of service frost resistance of ceramie tile it is best to use several parameters under multiple correlation with the parameter of service frost resistance. First Published Online: 14 Oct 2010